Long non-coding RNA ZFAS1 interacts with CDK1 and is involved in p53-dependent cell cycle control and apoptosis in colorectal cancer - Thorenoor, Nithyananda; Vychytilová, Petra; Hombach, Sonja; Mlčochová, Jitka; Kretz, Markus; Svoboda, Marek; Slabý, Ondřej (Oncotarget, 2016)
We determined expression of 83 long non-coding RNAs (lncRNAs) and identified ZFAS1 to be significantly up-regulated in colorectal cancer (CRC) tissue. In cohort of 119 CRC patients we observed that 111 cases displayed at least two-times higher expression of ZFAS1 in CRC compared to paired normal colorectal tissue (P < 0.0001). By use of CRC cell lines (HCT116+/+, HCT116-/- and DLD-1) we showed, that ZFAS1 silencing decreases proliferation through G1-arrest of cell cycle, and also tumorigenicity of CRC cells. We identified Cyclin-dependent kinase 1 (CDK1) as interacting partner of ZFAS1 by pull-down experiment and RNA immunoprecipitation. Further, we have predicted by bioinformatics approach ZFAS1 to sponge miR-590-3p, which was proved to target CDK1. Levels of CDK1 were not affected by ZFAS1 silencing, but cyclin B1 was decreased in both cell lines. We observed significant increase in p53 levels and PARP cleavage in CRC cell lines after ZFAS1 silencing indicating increase in apoptosis. Our data suggest that ZFAS1 may function as oncogene in CRC by two main actions: (i) via destabilization of p53 and through (ii) interaction with CDK1/cyclin B1 complex leading to cell cycle progression and inhibition of apoptosis. However, molecular mechanisms behind these interactions have to be further clarified.
Keywords: Aged; cyklin B1; regulace genové exprese u nádorů; vazba proteinů; Aged, 80 and over; RNA, Long Noncoding; RNA Interference; lidé; lidé středního věku; senioři; ženské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; Cyclin B1; Caco-2 buňky; nádorové buněčné linie; mužské pohlaví; western blotting; Blotting, Western; Cell Line, Tumor; Female; Poly(ADP-ribose) Polymerases; Kaplanův-Meierův odhad; G1 Phase Cell Cycle Checkpoints; kolorektální nádory; Adult; RNA interference; HCT116 Cells; Protein Binding; Middle Aged; Reverse Transcriptase Polymerase Chain Reaction; proteinkinasa CDC2; senioři nad 80 let; RNA dlouhá nekódující; Kaplan-Meier Estimate; CDC2 Protein Kinase; Humans; kontrolní body fáze G1 buněčného cyklu; poly(ADP-ribosa)polymerasy; buňky HT-29; nádorový supresorový protein p53; Apoptosis; Colorectal Neoplasms; dospělí; Gene Expression Regulation, Neoplastic; Male; Tumor Suppressor Protein p53; apoptóza; HT29 Cells; HCT116 buňky; Caco-2 Cells